An investigation into lexical stylistic devices in the work "A bright shining lie" by Neil Sheehan and its Vietnamese version - Đào Thị Bắc; Phan Văn Hòa, Assoc.Prof.Dr. (Đà Nẵng : The University of Da Nang, 2015)
Introduction; Literature review and theoretical background; Research design and Methodology; ...
M.A. thesis in social sciences and humanities. Field: The English language.Code: 60.22.02.01.
Includes references.
Keywords: The English language